P.W.D. Handbook: specifications, rates, tables, plates and notes / P.W. D Department: Nagpur Govt. Press 9th ed - Marryet, E. L
P.W.D. Handbook: specifications, rates, tables, plates and notes / P.W. D Department: Nagpur Govt. Press 624.102 P976e9 9th ed No. of Copies : 1